Elevated rates of HIV infection among young Aboriginal injection drug users in a Canadian setting - Kerr Thomas; Spittal Patricia M; Strathdee Steffanie A; Miller Cari L; Li Kathy; Schechter Martin T; Wood Evan (BMC, 2006)
Abstract Objectives Recent reports have suggested that Aboriginal and American Indian people are at elevated risk of HIV infection. We undertook the present study to compare socio-demographic and risk variables between Aboriginal and non-Aboriginal young (aged 13 - 24 years) injection drug users (IDUs) and characterize the burden of HIV infection among young Aboriginal IDUs. Methods We compared socio-demographic and risk variables between Aboriginal and non-Aboriginal young IDUs. Data were collected through the Vancouver Injection Drug Users Study (VIDUS). Semi-annually, participants have completed an interviewer-administered questionnaire and have undergone serologic testing for HIV and Hepatitis C (HCV). Results To date over 1500 Vancouver IDU have been enrolled and followed, among whom 291 were aged 24 years and younger. Of the 291 young injectors, 80 (27%) were Aboriginal. In comparison to non-Aboriginal youth, Aboriginal youth were more likely to test seropositive for either HIV (20% vs 7%, p=< 0.001) or Hepatitis C virus (HCV) (66% vs 38%, p =< 0.001), be involved in sex work and live in the city's IDU epi-centre at baseline. After 48 months of follow-up, Aboriginal youth experienced significantly higher HIV seroconversion rates than non-Aboriginal youth, 27.8 per ppy (95% CI: 13.4-42.2) vs. 7.0 per ppy (95% CI: 2.3-11.8) respectively (log-rank p = 0.005) and the incidence density over the entire follow-up period was 12.6 per 100 pyrs (CI: 6.49-21.96) and 3.9 per 100 pyrs (CI: 1.8-7.3) respectively. Interpretation These findings demonstrate that culturally relevant, evidence based prevention programs are urgently required to prevent HIV infection among Aboriginal youth.